Fasies dan Lingkungan Pengendapan Formasi Nanggulan di Sungai Kamal, Desa Pendoworejo, Kecamatan Girimulyo, Kabupaten Kulon Progo, Provinsi Daerah Istimewa Yogyakarta - Qoyyibi, Dava Saliham; Rizqi, Al Hussein Flowers (Retii, 2024)
So far, stratigraphic measurements on the Nanggulan Formation in the Nanggulan area have been limited to the Kalisonggo River location. There are also sedimentary rock outcrops with relatively steep slopes in the Kamal River. This location has been used as a study area to obtain a sized stratigraphic picture so that it can be studied as a basis for determining facies and environmental studies. deposition. The purpose of this research is to obtain measured stratigraphic data (measurement section) and aims to obtain relative ages and depositional environments. Administratively, the research area was carried out on the Kamal River, Pendoworejo Village, Girimulyo District, Kulon Progo Regency, Yogyakarta Special Region Province. Based on the research results, five (5) units in the stratigraphic data were measured using a sampling research method based on Jacob Stick stratigraphic measurements, including sandstone units, marl units, black mudstone units, siltstone units, and old andesite formation breccia units, prepared by reacting the samples using H2O2 solution, sample observation using a microscope, and determination based on data obtained using existing classifications. Based on plangtonic foraminifera analysis, the research location is aged N9-N11 (Middle Miocene). The depositional environment in the research area uses benthonic foraminifera identification which is then correlated to obtain a Middle Neritic depositional environment.